Pea (pisum sativum l.) breeding: advances of the breeding program at Universidad Nacional de Rosario - Gatti, Ileana (2021)
A pea breeding program to increase production in quantity and quality was started in 2005 in the College of Agrarian Sciences (FCA), National University of Rosario (UNR). The first steps were to gather an active collection of germplasm from around the world and to analyze genetic variability through morpho-agronomic and molecular traits in order to set objectives. In 2014, the National Institute of Agropecuarian Technology (INTA) and the FCAUNR, joined forces to unite inter-institutional efforts for promoting the local development of pea genotypes adapted to the region. This program, using conventional methodologies, has so far obtained a new commercial line (Primogénita FCA-INTA) of green cotyledons, semileafless, with high adaptation to local agro ecological conditions and high yield potential. Breeding, nevertheless, is a slow process. Developing new pea varieties usually takes a decade or more when using traditional methodologies; thus, different alternatives were proposed for the reduction of this period. Doubled haploids and in vitro culture have been some of the methodologies developed; in pulses, however, they have not been efficiently implemented in breeding programs. In this context, Speed Breeding emerges as a technology that allows increasing the efficiency of the programs, while reducing costs and the required labor.